U ok w dis?: Analysing language attitudes towards internet english - Abrahão, Viviane de Moraes (2014)
Language has been hugely affected by the ample use of the internet nowadays. Many of the characteristics of the “new language” created online are intrinsic to its needs, and many of them are seen as deviations or mistakes. However, there is no consensus to date of the real language attitude of users regarding this new type of language, its deviations and its creations. For that, it seemed necessary to develop a preliminary study on Language Attitudes towards Internet English, in order to analyze how users generally feel about this language. The results of a sociolinguistic questionnaire show that the attitude lies on the nature of the deviation; however, it is a general agreement that this new language is broadly used by teenagers, with very specific purposes online, and it is a tool for a faster typing.